Involvement of perinatal health professionals to reduce the exposure of pregnant women to chemicals. (30th September 2020) - Sauvant-Rochat, M; Bernard, L; Pelissier, M; Marie, C; Lémery, D; Vendittelli, F
Abstract: Background: During pregnancy, reducing exposure to chemicals is obvious to many pregnant women (PW), and also perinatal health professionals (PHP), but few of them are aware that these substances are present in everyday products (cleaning products, DIY products, gardening products, personal health care products, cosmetics, food plastic wrappers etc.). AIM: This study aimed to estimate the perception of risks related to chemicals by PW, and also to describe the advice provided by PHP to PW. Methods: A cross-sectional survey was performed among French PW. Interviewers, using a standardized questionnaire, collected data anonymously. Data focused on socio-demographic and occupational characteristics, perception of environmental risks, identification of chemicals by PW, and preventive advices performed by PHP. Statistical analysis (univariate analysis - logistic regression) were done with Modalisa® 8.0 software (Kynos, Paris). Results: 300 PW (29.5 +/- 5 years old) were included. They report a relatively high level of sensitivity to environmental issues (SE Score = 6.3 ± 1.7, on a Likert 0-10 scale). When asked about the level of risk associated with 15 environmental risks, pregnant women placed exposure to chemicals in only twelfth position. Two thirds of PW were interested by the composition of everyday products, and looked at the ingredients mentioned on the labels, but most of them declared that the information present on the labels were not comprehensible. An interest for organic products was noted. These behaviors were related to the age, socio-occupational status, perception of environmental risks. For most of PW, the main sources of information on chemicals were the Internet and medias. Only 5% PW identified PHP as potential interlocutors on this topic. Conclusions: For most PW, everyday products were not identified as health risk products. To date, it is important to strengthen the information provided to PW by PHP on the risks linked o chemicals during pregnancy. Key messages: Exposures to chemicals present in everyday products (DIY, cleaning products, cosmetics, food plastic wrappers etc.) are not well identified by pregnant women and by perinatal health professionals. Exposure to chemicals must be reduced during pregnancy and health promotion messages must integrate this advice to promote healthy behaviors.